The Influence of User-Generated Content (UGC) on Brand Trust and Purchase Intention of Local Fashion Products - Jopinus Saragih; Hendri Mayanta; Rosmita Purba (Mount Hope Economic Global Journal, 2025)
This study examines the effect of User-Generated Content (UGC) on brand trust and purchase intention for local fashion products in Indonesia. The research is motivated by the rapid growth of the local fashion industry alongside the challenge faced by local brands in building trust when competing with internationally resourced brands. Widely shared UGC on platforms such as Instagram and TikTok is expected to enhance engagement and drive purchase intention through mechanisms including social proof, source credibility, and cognitive/affective value processing. Using a mixed-methods design with a sequential explanatory approach, the study combines a quantitative survey phase with a qualitative phase involving netnography and interviews. The findings indicate that UGC significantly influences both brand trust and purchase intention. Specifically, UGC authenticity increases perceived credibility, which in turn strengthens brand trust; visual quality shapes aesthetic appeal and subsequently affects purchase intention; and social proof impacts purchase intention through normative influence. The effectiveness of UGC is also moderated by product involvement, platform type, and cultural relevance. The study further develops the Fashion Local UGC Impact Model (FLUIM), integrating UGC characteristics, creator attributes, platform dynamics, processing mechanisms, and outcomes in the form of trust and purchase intention. Practical implications are provided to help local fashion brands leverage UGC strategies that balance authenticity and quality, strengthen cultural relevance, and build engaged communities.